Skills For The Formation Of Conducting Skills In Choral Workshops In Students - Khujamkulov Pirimkul (Euro Asian Journal Publishing, 2024)
the article considers the concept of conducting techniques as a necessary element of the conducting and choral preparation of the future music teacher. During the course of the lesson, methods and methods of working on conducting techniques were identified in the preparatory and initial stages of teaching conducting techniques.
Keywords: conducting techniques; conductor-choral training